The man behind the evil. How Breivik killed without shame - Nielsen, Andrea Kiel (Politica, 2015)
How was Breivik able to carry out the terror attacks without any signs of guilt? An analysis of his motivation and his justification of the attacks explains that he prior to, during and after the attacks disengaged the moral self-regulatory mechanisms from his acts. A strong anti-Islamic ideology was a major source of justification for his acts. This enabled him to erase feelings of guilt and regret; it gave him a sense of pride and a grandiose self-image as a war hero, which matched his narcissistic tendencies.